Global research trends and hotspots in patellofemoral pain syndrome from 2000 to 2023: a bibliometric and visualization study - Xu, Jie; Cai, Zijuan; Chen, Meng; Wang, Xin; Luo, Xiaobing; Wang, Yanjie (Frontiers in Medicine, 2024)
Background Patellofemoral pain syndrome (PFPS) is a prevalent condition in sports medicine, and as sports competitions become more popular, the incidence of sports injuries is on the rise. Despite the increasing research on PFPS, there remains a lack of bibliometric analyses on this topic. The aim of this study was to identify the research hotspots and trends in the field of PFPS by reviewing 23 years of literature in this field. Methods By analyzing the literature on PFPS research from 2000 to 2023 in the core dataset of the Web of Science database and utilizing bibliometric tools like CiteSpace 6.1, VOSviewer 1.6.18, R-bibliometrix 4.6.1, Pajek 5.16, and Scimago Graphica 1.0.26, our aim was to gain insights into the current status and key areas of PFPS research. The study examined various aspects including the number of publications, countries, institutions, journals, authors, collaborative networks, keywords, and more. Through the visualization of relevant data, we also attempted to forecast future trends in the field. Results There were 2,444 publications were included in this visualization study, published in 322 journals by 1,247 authors from 818 institutions in 67 countries. The Journal of Orthopaedic and Sports Physical Therapy had the highest number of publications, with the USA leading in article count. La Trobe University contributed the most articles, while Rathleff MS and Barton CJ emerged as the most prolific authors. Hip and knee strength and core strength, lower extremity kinematics and biomechanics, females (runners), muscle activation, risk factors, gait retraining, clinical practice guidelines, and rehabilitation were research hotspot keywords. Conclusion Current research suggests that there is still significant potential for the development of PFPS research. Key areas of focus include the clinical effectiveness of combined hip and knee strengthening to address PFPS, characterization of lower limb kinematics and biomechanics, gait retraining, risk factors, and clinical practice guidelines. Future research could explore the effectiveness of innovative exercise therapies such as blood flow restricting training, gait retraining, and neuromuscular control training for PFPS improvement. Further investigation into gait retraining for runners, particularly females, and clinical efficacy study of a novel PRP formulation for the treatment of PFPS.